Academic Resilience as a Mediator in the Relationship between Academic Job Insecurity and Student Burnout - Agustin Andhika Putri (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
Job insecurity is common among students and is usually reflected in their worries or anxiety about their future job prospects. This study aims to examine the relationship between job insecurity and academic burnout, with academic resilience as a mediator. The subject selection method used purposive sampling, with Indonesian students experiencing anxiety about their future. The Job Insecurity Scale (JIS) was used in this study, with a Cronbach's α score of 0.88. Furthermore, the Maslach Burnout Instrument-Student Survey, with a Cronbach's α score of 0.80, was used to measure academic burnout. Finally, the Academic Resilience scale, with a Cronbach's α score of 0.90, was also used. The results indicate that academic resilience can reduce academic burnout, especially in students experiencing academic job insecurity.